2013
DOI: 10.1007/s13277-013-1358-y
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 genotypes influence prostate cancer susceptibility in Japanese Men

Abstract: This study aims to evaluate the relationship between the cyclooxygenase 2 (COX2) G1195A (rs689465) polymorphism and the risk of prostate cancer in a Japanese population and the associations between COX2 polymorphisms and clinicopathological characteristics, including Gleason grade and prostate-specific antigen (PSA) grade. We recruited 134 patients with prostate cancer and 86 healthy controls matched for age and smoking status. The COX2 G1195A polymorphism status was determined by polymerase chain reaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Our study is the first to evaluate the association between COX-1 (50C>T) polymorphism and prostate cancer risk, whereas several previous reports were available for the association between COX-2 (-1195G>A) polymorphism and prostate cancer risk. Our study results were in agreement with Sugie et al [ 28 ] in a Japanese population, but Wu et al (Taiwan) [ 29 ], Cheng et al (USA) [ 30 ], and Kopp et al (Denmark) [ 13 ] showed the absence of risk association between COX-2 (-1195G>A) polymorphism and prostate cancer risk.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is the first to evaluate the association between COX-1 (50C>T) polymorphism and prostate cancer risk, whereas several previous reports were available for the association between COX-2 (-1195G>A) polymorphism and prostate cancer risk. Our study results were in agreement with Sugie et al [ 28 ] in a Japanese population, but Wu et al (Taiwan) [ 29 ], Cheng et al (USA) [ 30 ], and Kopp et al (Denmark) [ 13 ] showed the absence of risk association between COX-2 (-1195G>A) polymorphism and prostate cancer risk.…”
Section: Discussionsupporting
confidence: 93%
“…This results in hyperproliferation, transformation, tumor growth, invasion, and metastasis, thus potentially increasing the risk for PCa 19. One study reported Cox-2 overexpression not in tumor tissue but rather in proliferative inflammatory atrophy, a putative precursor lesion of PCa with a high correlation with HGPIN 2021. In addition, a recent review identified E-cadherin, a protein regulated by Cox-2, as a prognostic indicator in PCa with a strong correlation between E-cadherin dysfunction and BCR using TMAs in patients with clinically localized PCa after RP 14…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits apoptosis of cancer cells, reduces cell adhesion and induces angiogenesis, making it easier for the cancer cells to invade small blood vessels and lymphatic tube and metastasize (31,32). COX-2 has been extensively studied as an inducible expression protein and has been detected in various tumor tissues such as pancreatic cancer, colorectal carcinoma, non-small lung cancer positively correlates with tumor invasion and lymphatic metastasis (33,34). We then detected the effects of CpG ODN and CQ on mRNA expression of MMP-2, MMP-7 and COX-2.…”
Section: Discussionmentioning
confidence: 99%